Development of a Structure Peer Counseling Model to Improve Assertive Behavior Among Junior High School Student - Nurmastuti, Fitria; Sanyata, Sigit; Prawati, Rita (Suluh: Jurnal Bimbingan dan Konseling, 2026)
Background: Many junior high school students exhibit low assertiveness, particularly in expressing opinions, resisting negative peer pressure, and maintaining interpersonal boundaries, which may hinder their socio-emotional development. Aim: This study examined the urgency and effectiveness of structured peer counseling as an intervention to improve assertive behavior among junior high school students. Method: The research employed a quasi-experimental pretest–posttest control-group design involving 62 students, divided into an experimental and a control group. The intervention consisted of structured peer counseling sessions emphasizing active listening, empathy, modeling, and role-playing of assertive communication. Assertive behavior was measured using a four-point Likert scale instrument administered before and after the intervention. Data were analyzed using the Wilcoxon Signed-Rank Test to determine differences between pretest and posttest scores. Results and Discussion: The findings revealed a statistically significant improvement in the experimental group (Z = -4.643, p < 0.001) with a large effect size (r = 0.60), indicating meaningful behavioral change following peer counseling. In contrast, the control group did not show a significant improvement (Z = -1.924, p = 0.054). These results suggest that structured peer counseling provides an effective developmental context for practicing assertive communication skills through peer interaction and social modeling. Conclusion: The study confirms the urgent need for assertive behavior intervention in junior high schools and demonstrates that structured peer counseling is an effective approach to enhancing students’ assertiveness, providing empirical support for its integration into school guidance and counseling programs.